2002
DOI: 10.1002/cne.10488
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal development in larval polychaete Phyllodoce maculata (Phyllodocidae)

Abstract: The existing view on neuronal development in polychaetes, as undergoing neurogenesis beginning in the rudiments of central ganglia and then extending peripherally, has been contrasted with the latest findings in molluscs, their sister trochozoan group, which show a peripheral to central mode of neurogenesis. The current study addresses this issue by examining early neuronal development in the polychaete Phyllodoce maculata using immunolabeling against acetylated alpha-tubulin, serotonin, and the FMRFamide. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 44 publications
6
114
1
1
Order By: Relevance
“…Furthermore, the serotonergic and FMRFamidergic immunoreactivity in P. massiliensis only originates in anterior regions. For P. dumerilii and most other annelid larvae, the origin of FMRFamidergic immunoreactivity is described to appear at the anterior pole, whereas serotonin immunoreactivity can be found first at the posterior pole (Voronezhskaya et al, 2003;Orrhage and Müller, 2005;Wanninger et al, 2005;McDougall et al, 2006;Brinkmann and Wanninger, 2008;Kristof et al, 2008;Fischer et al, 2010;Helm et al, 2013;). Similarly, the serotonergic immunoreactivity is detectable first…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the serotonergic and FMRFamidergic immunoreactivity in P. massiliensis only originates in anterior regions. For P. dumerilii and most other annelid larvae, the origin of FMRFamidergic immunoreactivity is described to appear at the anterior pole, whereas serotonin immunoreactivity can be found first at the posterior pole (Voronezhskaya et al, 2003;Orrhage and Müller, 2005;Wanninger et al, 2005;McDougall et al, 2006;Brinkmann and Wanninger, 2008;Kristof et al, 2008;Fischer et al, 2010;Helm et al, 2013;). Similarly, the serotonergic immunoreactivity is detectable first…”
Section: Discussionmentioning
confidence: 99%
“…A pair of ''pioneer'' nerve cells at the pygidium with axons extending forwards to the prototroch has been observed in 48-hours metatrochophores of Platynereis (Dorresteijn et al,'93) and a single such cell has been observed in an early stage of Phyllodoce (Voronezhskaya et al, 2003), and also in early larvae of Serpula oregonensis (by Dr. Stephen Kempf and the author). The significance of these cells is unknown.…”
Section: Apical Organ and Adult Brainmentioning
confidence: 98%
“…Anatomical studies have revealed that larval ciliary bands receive extensive innervation from the nervous system, both in Platynereis and in other species (21). In protostome larvae, neurons expressing the neuropeptide FMRF-amide often contribute to this innervation (22)(23)(24). Neurons with related Famide neuropeptides also innervate ciliary bands in sea urchin larvae (25), suggesting that neuropeptides may have a general role in the regulation of larval locomotion in both protostomes and deuterostomes.…”
mentioning
confidence: 99%